Innate lymphoid cells in allergy - Koyasu, Shigeo (Henry Stewart Talks, 2024)
Innate Lymphoid Cells (ILCs), Allergy and ILCs, Type 1 and 2 cytokine responses, Innate and adaptive immunity, Asthma, Lung eosinophilia, Mucus secretion, Helminth infection and allergic inflammation, Epithelial cell-derived IL-33 and IL-25, Lung inflammation by papain, TSLP-STAT5 axis, Corticosteroid sensitivity, Interferons (IFNs) and ILCs